ROSUVASTATIN MAY LOWER VASCULAR DEMENTIA RISK (World Bulletin of Public Health, 2024)
Cognitive impairment is common in older people with ischemic heart disease. The first reason is dyslipidemia-distributed atherosclerosis, and the second reason is impaired pumping function of the heart in heart failure. In dyslipidemia, the amount of antiatherogenic lipids increases. The most effective drug in this case is rozurvastatin. Rosurvastatin reduces the size of atherosclerotic plaques not only in the heart, but also in the brain, improves blood circulation and blood supply to cells, therefore it can reduce the risk of dementia in the elderly
Keywords: Rosurvastatin; ischemic heart disease; Cognitive impairment